A Letter from the Editors: Pearls and Pitfalls for Writing a Methods Section. (17th February 2023) - Crowe, Remle P.; Cash, Rebecca E.
Abstract: The Methods section is the core of any research manuscript, yet writing this section may feel like a daunting task. In this letter, two of our methods and statistics editors provide some guidance on common pitfalls to avoid and pearls for writing the Methods section. From study design to analytic approach, this letter gives a high-level look at keys to success.